Behaviour of concrete by partial replacement of fine aggregate with eco sand. (2022) - Vinodhini, C.; Anandaraj, S.; Karthik, S.; Dharmaraj, R.; Sivabharathi, R.; Sivaganesh, P.; Sivasankar, M.B.; Yogesh, V.
Abstract: Within the current period, an outsized quantity of concrete construction activities is happening. Natural sand (river sand) which is the key ingredient of concrete is changing into demand and high-ticket. Factory-made sand may be substitute of concrete construction which has been produced from crushing laborious batholite rock. Eco-Sand which is a by-product from cement manufacturing. The entire study deals with the behaviour of concrete by replacing sand with eco sand. The traditional watercourse sand is replaced with M sand an in this study factory made sand is replaced by Eco-Sand at numerous percentages like 6%, 12%, 18%, 24%& 30% in PCC. It's valued that the optimum replacement shares of Factory-made Sand by Eco-Sand and also the properties of contemporary concrete, laborious concrete in PCC with Eco-Sand. Most scope of this study is to cut back the pollution and environmentally friendly. Varied test provides that eighteen percentages as the optimum percentage of the current mix of the factory made sand and Eco-sand.